RELIGIOUS SCRIPTURES - Pathil, Kuncheria (Journal of Dharma, 1996)
All the World Religions have their own sacred Scriptures which are the authoritative sources for their teachings and practices. Almost all the Scriptures claim to have a divine origin either directly or indirectly. But approaches to Scriptures differ from religion to religion. -For many religions, Scriptures contain the Word of God or Utterances of God, given to humans for their guidance and salvation. Most of these Scriptures existed first in oral traditions and later written down by human agents who often claimed to have a divine inspiration. Some religions have their beginnings in the Enlightenment of their founders, and the original experience of these founders was passed on to their disciples and later generations through oral and written traditions which became later their sacred Scriptures. Their authority derive from the authority of their founders.